2001
DOI: 10.1002/ajh.10026
|View full text |Cite
|
Sign up to set email alerts
|

Study of the single nucleotide polymorphism (SNP) at the palindromic sequence of hypersensitive site (HS)4 of the human β‐globin locus control region (LCR) in Indian population

Abstract: LCR, a genetic regulatory element, was examined in b-thalassemia patients who do not show any mutation in the b-globin genes. We sequenced LCR-HS2, HS3, and HS4 in samples from 16 such patients from the Indian population and found only one SNP A-G in the inverted repeat in HS4. A signi®cant association was observed between the G allele and occurrence of b-thalassemia by Fisher's exact test. The AG and GG genotypes showed higher relative risk as compared to the AA genotype. We also observed linkage disequilibri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
6
0

Year Published

2002
2002
2008
2008

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 20 publications
(8 citation statements)
references
References 6 publications
2
6
0
Order By: Relevance
“…Taken together, these findings imply that the genetic basis of inter-individual differences in GH1 gene expression is likely to be extremely complex. In this regard, our results are also reminiscent of the b-globin LCR in which SNPs have been previously reported in the HS2 and HS4 regions [Perichon et al, 1993;Kukreti et al, 2002], with different alleles of the HS2 SNP conferring different levels of enhancement upon the expression of a gglobin promoter-linked reporter gene [Ofori-Acquah et al, 2001].…”
Section: Discussionsupporting
confidence: 73%
“…Taken together, these findings imply that the genetic basis of inter-individual differences in GH1 gene expression is likely to be extremely complex. In this regard, our results are also reminiscent of the b-globin LCR in which SNPs have been previously reported in the HS2 and HS4 regions [Perichon et al, 1993;Kukreti et al, 2002], with different alleles of the HS2 SNP conferring different levels of enhancement upon the expression of a gglobin promoter-linked reporter gene [Ofori-Acquah et al, 2001].…”
Section: Discussionsupporting
confidence: 73%
“…The observed variations led to allelic variability, both in base composition and in the length of the repeat, and they add an element to the genetically variable environment of the ␤-thalassemia chromosome. Sequence analysis of the 462-bp HS2 fragment, including the highly polymorphic (AT) x N y (AT) z motif of the ␤-LCR, showed polymorphisms identical to those described previously [16,17] and occurred in three different sequence configurations of the (AT) x N y (AT) z motif: (AT) 1 0 N 1 2 (AT) 1 1 , (AT) 9 N 12 (AT) 11 , (AT) 9 N 12 (AT) 10 specific to the genotype of the SNP at the palindromic region of HS4 of the ␤-LCR. It was observed that the G allele of ␤-LCR HS4 is associated with only one distinct polymorphic pattern of AT-rich segments, (AT) 9 N 12 (AT) 10 of the LCR HS2 region [17] (Table IV), indicating these mutational events were probably rare and arose from a common founder.…”
Section: Polymorphic Sites In ␤-Lcr Hs1 ␤-Lcr Hs2 ␤-Lcr Hs3 and ␤-supporting
confidence: 74%
“…We observed from automated genotyping and direct sequence analysis that the G allele in the palindromic sequence of the HS4 locus is a s s o c i a t e d w i t h o n l y o n e d i s t i n c t p a t t e r n , (AT) 9 N 12 (AT) 10 , of HS2 of the ␤-LCR. There appears to be linkage disequilibrium at the two loci with the pre- ponderance of occurrence of the G allele at HS4 along with the (AT) 9 N 12 (AT) 10 allele at the HS2 locus of ␤-LCR, suggesting that the G allele could be an evolutionarily new mutation in the study population [17]. There are reports that sequence variations in the HS2 region of ␤-LCR are associated with altered levels of fetal hemoglobin [16] in the thalassemia intermediate patients.…”
Section: Discussionmentioning
confidence: 95%
“…Dyad symmetry sequences are present close to the four DNase I hypersensitive site (HS) in the β-globin LCR. More recent studies ( 24 ), on the spectrum of β-thalassemia mutation and their association with allelic sequence polymorphism at the human β-globin gene cluster have revealed a single nucleotide polymorphism (SNP) at the quasipalindromic sequence of HS4 of the LCR. The studies carried out on Indian population showed an A → G polymorphism in the sequence d-TGGGG(A/G)CCCCA ( 24 ).…”
Section: Introductionmentioning
confidence: 99%